2001
DOI: 10.1111/j.1365-2621.2001.tb16093.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin a Most Likely Inducer of Black Spots in Kuruma Prawn Penaeus japonicus During Storage

Abstract: Hemocyanin (Hc) from plasma of kuruma prawn was characterized as a potent inducer of black spots during storage. An oxygen transporter, hemocyanin was converted into phenoloxidase (PO)-like enzyme (HdPO) with SDS treatment as well as prophenoloxidase isolated from hemocytes. Both enzymes showed similar biochemical properties. The isolated PO, however, was so unstable that its activity was drastically reduced when frozen and thawed at -25 ЊC for less than a week, while HdPO completely retained its activity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 30 publications
6
42
0
Order By: Relevance
“…32 Kuruma prawn (Penaeus japonicas) hemocyanin can also gain the phenolase activity by the addition of sodium dodecyl sulfate to the solution. 33 However, these activation processes are so complicated that neither the regulation process of the enzymatic functions nor the mechanism of the phenolase and catecholase activities had been addressed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…32 Kuruma prawn (Penaeus japonicas) hemocyanin can also gain the phenolase activity by the addition of sodium dodecyl sulfate to the solution. 33 However, these activation processes are so complicated that neither the regulation process of the enzymatic functions nor the mechanism of the phenolase and catecholase activities had been addressed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The melanosis-inhibiting effect of 4-hexylresorcinol accompanied by several organic acids and chelating agents, has also been reported in prawns (Montero et al, 2001). Adachi et al (2001) have also reported a significant and rapid development of black spots in Kuruma prawn after thawing. Shrimp treated with 4-hexylresorcinol showed the best appearance during conservation, with only a slight melanosis over a minimum of 8 days.…”
Section: Organoleptic Analysismentioning
confidence: 88%
“…The second showed conversely that Hc in crabs and lobsters has o-diphenol oxidase activity when treated with perchlorate [10]. In 2001, based on those two facts, prawn Hc was shown to be converted into a PO-like enzyme by dodecyl sodium sulphate (SDS) [9]. In addition, this catalytic activity is very stable and is maintained over two months under frozen conditions, while PO loses its activity within a week under the same conditions ( Fig.…”
Section: The Relationship Of Po and Melanogenesis In Prawnsmentioning
confidence: 94%
“…The effects of the freeze-thawing process on this system remain unclear, but it is believed that this system is strictly controlled in the living body and breaks down post-mortem to spontaneously activate proPO to PO. difficult [7][8][9]. The details of characterisation of proPO are described by Cerenius and Söderhäll [3].…”
Section: Biochemical Characterisation Of Propo and Pomentioning
confidence: 99%